AMBRA1 and its role as a target for anticancer therapy - Li, Xiang; Lyu, Yuan; Li, Junqi; Wang, Xinjun (Frontiers in Oncology, 2022)
The activating molecule in Beclin1-regulated autophagy protein 1 (AMBRA1) is an intrinsically disordered protein that regulates the survival and death of cancer cells by modulating autophagy. Although the roles of autophagy in cancer are controversial and context-dependent, inhibition of autophagy under some circumstances can be a useful strategy for cancer therapy. As AMBRA1 is a pivotal autophagy-associated protein, targeting AMBRA1 similarly may be an underlying strategy for cancer therapy. Emerging evidence indicates that AMBRA1 can also inhibit cancer formation, maintenance, and progression by regulating c-MYC and cyclins, which are frequently deregulated in human cancer cells. Therefore, AMBRA1 is at the crossroad of autophagy, tumorigenesis, proliferation, and cell cycle. In this review, we focus on discussing the mechanisms of AMBRA1 in autophagy, mitophagy, and apoptosis, and particularly the roles of AMBRA1 in tumorigenesis and targeted therapy.